Analysis of a Chilean School Mental Health Program from Stage Implementation Framework - Samuel; López-Donaire, Valentina; Meza-Ibarra, Marcela; Parra Moraga, Bárbara; Prosser Bravo, Gabriel; Caro Zúñiga, Camilo; Rojas-Andrade, Rodrigo (Revista de Psicología, 2022)
This study analysed the implementation stages of the Skills for Life (HPV, in Spanish) program of the National Board of School Aid and Scholarships, Chile. For this purpose, it was used a mixed descriptive exploratory sequential design, through a triangulation of information from the Stage Implementation Framework created by the Active Implementation Research Network. This was based on the information emerging from a bibliometric review of the scientific production of HPV and historical facts of the program obtained from semi-structured interviews with decision-makers. We found 35 scientific articles published between the years 1995 and 2020, and a series of historical milestones between 1991 and 2016, which were analysed and classified into Exploration, Installation, Initial Implementation, Full Implementation or Sustainability phases. Finally, it is identified that the program took three times longer (17 years) than theoretically indicated (four to six years) to reach the sustainability phase, due to a series of contextual factors, such as: difficulties in the transfer of technical knowledge to practice, insufficient and oscillating financing, national coordination with few human resources dedicated to multiple tasks and a displacement of the program in the public agenda.